Kajian Filsafat Moral Kant Pada Kode Etik Auditor Internal Pemerintah - Fakhmol Risepdo; Erina Sudaryati (Politeknik Ganesha Medan, 2023)
This study aims to analyze in depth the values of the code of ethics of government internal auditors (APIP) using moral philosophy studies. The research method used is a literature study of various types of research related to the code of ethics of APIP and study of moral philosophy in the last five years. This literature study uses research articles published in indexed journals on the Garuda portal and google scholar. Data is collected using keywords, such as: “government internal auditors (APIP)”, “moral philosophy”, “APIP’s code of ethics”, and others. The results of research show that the study of Kant’s moral philosophy can provide a deeper understanding of the fundamental meanings of the APIP’s code of ethics. Kant’s moral philosophy introduces an ethical obligation to measure morality through an action or deed. In the context of APIP’s code of ethics it can be seen that APIP’s good deeds are reflected by the correct implementation of the code of ethics.